Vocabulary of Political Discourse at the English Lessons - R. Gagarina, Vilena; V. Shelestova, Olga; P. Sheinina, Dina; Vasallo Baez, Irian (International Journal of Criminology and Sociology, 2022)
Teaching English is based on the development and improvement of lexical skills, the appropriate use of words, phrases, idioms that are most suitable for describing a particular situation. Understanding words and expressions allows us to convey the meaning of our intentions in the process of communication. The goal of a teacher of a foreign language is to gradually expand the vocabulary of the student and activate the studied vocabulary by organizing a system of exercises that stimulate communicative expressions. «The secondary language personality is viewed by modern linguistics as abilities to communicate in foreign languages. It is difficult to overestimate the importance of that conclusion for the process of teaching a foreign language as it assumes basic distinctions in the choice of teaching methods for various groups of language learners». One of the major problems in learning English is listening comprehension. This problem is faced not only by beginners, but also people with a high level of knowledge. One of the effective teaching methods is to include video materials in the learning process at the English lessons.